Estruturação da comunidade de microcrustáceos (Copepoda, Ostracoda) associados a ambientes de fitotelmata em Nidularium innocentii Lem. (Bromeliaceae). - Lopes Filho, Danilo Rezende (2021)
Since the classic Forbes publication “The Lake as a Microcosm” in 1887, scientific research on freshwater ecosystems has been boosted due to the formulation of the first limnological concepts. For a long period, scientific research aimed at the spatial distribution of communities was focused on large water bodies, leaving aside studies in small freshwater environments, such as bromeliad phytotelmata. The first work of this thesis carried out a scientometric analysis in virtual databases on bromeliad phytotelmata, and 140 publications were found. South America was the region with the highest number of articles published. Most articles presented predictive designs, focusing on community ecology. Insecta was the most recorded group of organisms. In the second article, it was investigated how the microcrustacean community (composition, abundance and richness) is associated with the phytotelmata of Nidularium innocentii Lem. was influenced by the limnological variables present along the altitudinal gradient. The study was carried out in Serra da Prata, in the state of Paraná. The results did not show a distribution pattern in species richness along the altitudinal gradient, refuting the central domain effect hypothesis among others. However, there were dissimilarities in the composition of microcrustacean species in relation to altitudes. The different climatic types and vegetation types directly influenced the environmental variables in the phytotelmata microcosms, leading to similarities in species composition between altimetric elevations located in the same climatic region and dissimilarities between different climates.